2021
DOI: 10.48550/arxiv.2105.04638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Missing Metal Problem in Galaxy Clusters: Characterizing the Early Enrichment Population

Abstract: Rich and poor galaxy clusters have the same measured halo metallicity, 0.35-0.4 Z , despite being an order of magnitude apart in stellar fraction, M * /M gas . The measured ICM metallicity in rich clusters cannot be explained by the visible stellar population as stars make up only 5% of the total gas mass. The independence of metallicity from M * /M gas suggests an external and universal source of metals such as an Early Enrichment Population (EEP). Galaxy cluster RX J1416.4+2315 has the lowest stellar fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A conundrum in the enrichment study is that the total metals observed in rich clusters cannot be explained by the visible stellar component, as shown in Figure 4 (also see E Blackwell et al 2021;Ghizzardi et al 2021). This discrepancy invokes an external and universal source of metals even before the star formation episode -an Early Enrichment Population (EEP), which is not visible today (Mantz et al 2017).…”
Section: Early Enrichment Populationmentioning
confidence: 99%
“…A conundrum in the enrichment study is that the total metals observed in rich clusters cannot be explained by the visible stellar component, as shown in Figure 4 (also see E Blackwell et al 2021;Ghizzardi et al 2021). This discrepancy invokes an external and universal source of metals even before the star formation episode -an Early Enrichment Population (EEP), which is not visible today (Mantz et al 2017).…”
Section: Early Enrichment Populationmentioning
confidence: 99%
“…5.3, in the sense that the metal content of hot atmospheres at all scales would have very little to do with their associated stellar population (see e.g. Blackwell et al 2021). However, such a preenrichment scenario would hardy explain the narrow metal peak present in the core of NGC 1404, and would ignore the whole content of metals produced more recently which, in one way or another, must be present in its galactic atmosphere.…”
Section: The Chemical History Of Ngc 1404mentioning
confidence: 99%
“…Thirdly, when assessing the Sivanandam et al (2009) result that the ICS produces 25 per cent of the cluster ICM metallicity, Blackwell et al (2021) point out that, if this were the case, studies would show the ICS accounting for 80 per cent of the total cluster light, which is four times greater than what is currently observed. On this point, it is worth noting that Blackwell et al (2021) suggest the above result of Sivanandam et al ( 2009) is four times too high, while we find a value for the same fraction around four to five times lower than Sivanandam et al (2009).…”
Section: Ics Mass Fractionsmentioning
confidence: 92%